Clinical Characteristics of Different Primary Constipation Subtypes in a Chinese Population. Issue 7 (August 2020) - Jiang, Ya; Tang, Yurong; Lin, Lin
Abstract : Goal: To investigate the clinical characteristics of different primary constipation subtypes, including symptom clusters, psychological problems, quality of life (QOL), and to explore the role of constipation symptoms and the mental state in the QOL of constipation subtypes. Background: Patients with chronic constipation (CC) may be unsatisfied with their therapy and suffer recurrent symptoms. Different constipation subtypes require different treatments; therefore, it is important to identify the features of different constipation subtypes. Study: CC patients (n=206) visiting our gastroenterology clinic were studied. CC subtypes were diagnosed using the Rome-IV criteria. We used validated questionnaires to investigate the symptom severity, mental state, and QOL of patients. QOL was assessed with the Patient Assessment of Constipation Quality of Life (PAC-QOL) and SF-36 questionnaire. Results of symptom, mental and QOL scores are expressed as means with 95% confidence interval. Results: Three groups of CC patients differed in their constipation scoring system and the Patient Assessment of Constipation Symptoms (PAC-SYM) total scores, and both were significantly higher in the functional defecation disorder (FDD) group compared with that in the normal transit constipation (NTC) group. FDD patients tended to have more severe "abdominal symptoms, " "rectal symptoms" than NTC group. No significant difference in General Anxiety Disorder 7-item or Patient Health Questionnaire-9 results was found among the 3 groups. Significantly more patients with FDD suffered more "physical discomfort" and had poorer QOL in the "physical function" dimension of SF-36. FDD and NTC patients mainly showed associations between CC-related QOL and constipation severity, while slow transit constipation patients' QOL was significantly associated with anxiety and depression. Conclusion: Patients with FDD suffer more severe constipation symptoms and have a lower QOL than patients in other CC subgroups. FDD and NTC patients' QOL is mainly linked to constipation symptoms, while that of slow transit constipation is mainly related to mental states such as anxiety and depression.